Інтродукція, збереження та збагачення біорізноманіття рослин у Національному ботанічному саду ім. М.М. Гришка НАН України - Zaimenko, N.V.; Cherevchenko, T.M.; Gaponenko, M.B.; Rakhmetov, G.B. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2015)
The paper deals with the main achievements of scientists of M.M. Gryshko National Botanical Garden of the NAS of Ukraine (NBG) in scientific, conservation, cultural and educational activities. The results of researches on biodiversity, conservation, plants protection, introduction, acclimatization and selection, allelopathy, medical botany, landscape design, bioindication and hemosystematycs are given. It is noted that over 14 thousands species, forms and varieties of plants, are collected in NBG, and the most unique collections attributed to the objects of national heritage. Breeders have obtained more than 300 certificates or author ship on plant varieties. NBG carries out extensive international cooperation, several new exposition of plant collection appeared in Botanical Garden. In recent years the achievements of NBG scientists were awarded by two State Awards in the field of science and technology of Ukraine.